Off-Broadway musicals since 1919 : from Greenwich Village follies to The toxic avenger - Hischak, Thomas S. (Scarecrow Press, 2011)
Although the venue Off Broadway has long been the birthplace of innovative and popular musicals, there have been few studies of these influential works. Long-running champs, such as The Fantasticks and Little Shop of Horrors, are discussed inmany books about American musicals, but what of the hundreds of other Off-Broadway musicals? In Off-Broadway Musicals since 1919, Thomas Hischak looks at more than 375 musicals, which are described, discussed, and analyzed subjectively, with particular attention given to their books, scores, performers, and creators. Presented chronologically and divided.